DNA methylation and genetic degeneration of the Y chromosome in the dioecious plant Silene latifolia - Rodríguez Lorenzo, José Luis; Hobza, Roman; Vyskot, Boris (BMC genomics, 2018)
BACKGROUND: S. latifolia is a model organism for the study of sex chromosome evolution in plants. Its sex chromosomes include large regions in which recombination became gradually suppressed. The regions tend to expand over time resulting in the formation of evolutionary strata. Non-recombination and later accumulation of repetitive sequences is a putative cause of the size increase in the Y chromosome. Gene decay and accumulation of repetitive DNA are identified as key evolutionary events. Transposons in the X and Y chromosomes are distributed differently and there is a regulation of transposon insertion by DNA methylation of the target sequences, this points to an important role of DNA methylation during sex chromosome evolution in Silene latifolia. The aim of this study was to elucidate whether the reduced expression of the Y allele in S. latifolia is caused by genetic degeneration or if the cause is methylation triggered by transposons and repetitive sequences. RESULTS: Gene expression analysis in S. latifolia males has shown expression bias in both X and Y alleles. To determine whether these differences are caused by genetic degeneration or methylation spread by transposons and repetitive sequences, we selected several sex-linked genes with varying degrees of degeneration and from different evolutionary strata. Immunoprecipitation of methylated DNA (MeDIP) from promoter, exon and intron regions was used and validated through bisulfite sequencing. We found DNA methylation in males, and only in the promoter of genes of stratum I (older). The Y alleles in genes of stratum I were methylation enriched compared to X alleles. There was also abundant and high percentage methylation in the CHH context in most sequences, indicating de novo methylation through the RdDM pathway. CONCLUSIONS: We speculate that TE accumulation and not gene decay is the cause of DNA methylation in the S. latifolia Y sex chromosome with influence on the process of heterochromatinization.
Keywords: listy rostlin; exprese genu; DNA Methylation; Gene Expression; Sequence Homology, Nucleic Acid; Silene; metylace DNA; Silene latifolia; sekvenční homologie nukleových kyselin; Epigenetics; molekulární evoluce; Evolution, Molecular; chromozomy rostlin; Immunoprecipitation; Chromosomes, Plant; DNA rostlinná; DNA methylation; Y degeneration; DNA, Plant; Plant Leaves; Sodium bisulfite; Sex-linked genes; Sex chromosomes